The Political economy of foreign investment in Latin America : dependency revisited - Higginbottom, Andy (2013)
Uses quantitative data as evidence of a distinction between two groups in the sub-region, one which is openly collusive with foreign capital and the other which seeks to regulate and contain the penetration of global capital.